Catholic citizen education :el salvador 1832-1880 - González Torres, Julián (2013)
In this paper, the author analyzes the way in which the Salvadoran State, during the years 1832 to 1880, intended to shape a kind of Catholic citizen, starting from elementary school. The research shows that such system educated the children (future citizens) for eternal life (celestial) instead of training them for the tasks of the State. Nevertheless, the Salvadoran State (at least until 1880) saw in the Catholic religion the most suitable form to shape the citizens that the fatherland demanded.  The education of the lay citizen would start until the decade of 1880, having as a precedent the teaching of political catechism, which was made official in the decade of 1870.